Omnibus law policy and motivation's impact on employee performance at PT XYZ - Novialumi, Anita; Winata, Siti Dewi; Sukirno, Sukirno; Wiladiyah, Lala; Er, Luthvi Rachman (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
This study aims to gain a deeper understanding of how employees perform their jobs and identify the broad legal framework that affects PT. XYZ. A diverse group of respondents participated in the saturated sampling strategy. The findings from the regression analysis show a significant correlation between the examined factors and employee performance. This regression model assesses the Omnibus Law, employee work performance, and motivation. The results of the regression tests indicate that the Omnibus Law has a considerable impact on employee performance, although with a relatively low significance level. Additionally, the motivation factor has a noteworthy positive effect on staff performance. The study's findings have key implications for PT. XYZ and similar organizations. First, the Omnibus Law's impact on employee performance highlights the need for training and compliance resources. Second, motivation and encouraging managers to establish recognition programs and career development opportunities are crucial. Lastly, the minimal impact of the Omnibus Law suggests that legal frameworks are not the sole performance influencers, prompting organizations to embrace a holistic approach that combines legal compliance with leadership support, workplace culture, and employee well-being initiatives.